Growth and Optical Homogeneity of Hf:Mn:Fe:LiNbO3 Crystals with Various ［Li］/［Nb］ Ratios - DAI Li; HE Keqi; HAN Xianbo; WANG Yuning (Journal of Harbin University of Science and Technology)
The Hf:Mn:Fe:LiNbO3 crystals were grown with various ［Li］/［Nb］ ratios (0946, 105, 120 and 138) by the Czochralski method In order to explain the influence of different ［Li］/［Nb］ ratios for the defect structure of Hf:Mn:Fe:LiNbO3 crystals, the segregation coefficients of the Hf4+, Fe3+ and Mn2+ ions in the crystals were carried out with an inductively coupled plasmaatomic emission spectrometer, and we analyze the optical homogeneity of Hf:Mn:Fe:LiNbO3 crystals by the birefringence gradient method The result show that the segregation coefficients of the Hf4+ ions increase to 10 nearly when ［Li］/［Nb］ ratios is 138, and the ［Li］/［Nb］ ratios of increase in the crystal with the ［Li］/［Nb］ ratios increase in the melt Hf:Mn:Fe:LiNbO3 crystals have better optical homogeneity when ［Li］/［Nb］ ratios achieve 138 This experimental result is explained by the occupancy mechanism of LiNbO3 crystals and lithium vacancy defect